Lived Experiences of Female Academics: How Social Support Shapes Work-Life Balance in Indonesian Higher Education - Mariyani, Devi; Ayriza, Yulia; Triyanto, Deni; Lestari, Ditha (Jurnal Psikologi, 2025)
This study explores how social support influences the work-life balance of female academics in Indonesian higher education. Using a qualitative phenomenological approach, twenty lecturers shared their experiences in balancing academic responsibilities (Tri Dharma) with family life. Thematic analysis revealed four key forms of social support: (1) family instrumental support, which enables academics to perform their academic tasks more effectively, (2) institutional flexibility, which reflects recognition and trust, creating a supportive work environment that accommodates the demands of both professional and personal life, (3) collegial emotional support, fostering a shared space of empathy, solidarity, and resilience among colleagues, and (4) the integration of instrumental and emotional support, which promotes personal growth, alleviates stress, and enhances work-life harmony. These findings extend Sarafino’s theory of social support by revealing a culturally embedded hierarchy of support within the collectivist context of Indonesian academia, where family, colleagues, and institutions each play distinct roles in providing the necessary resources. The study highlights how social relationships and institutional structures co-construct the well-being of female academics, emphasizing the interdependent nature of both formal and informal support systems. By offering insights into how these dynamics shape work-life balance, this research provides valuable recommendations for gender-responsive policies and practices in higher education. Such policies can improve the work-life balance, career satisfaction, and overall well-being of women in academia, contributing to a more equitable and supportive academic environment.